Dự án đa dạng hóa nông nghiệp - The World Bank in Vietnam (WB) (Hà Nội, 2003)
The Agricultural Diversification Project aims to diversify and intensify agricultural production so as to increase and stabilize farmers' incomes and rural employment in the poor central highland and coastal provinces of Vietnam. The project has four components. Component 1 helps small farmers plant and maintain new rubber trees in ten central provinces; rehabilitates small rubber holdings in eight central provinces; upgrades existing and constructs new farm tracks to transport inputs; provides technical support for land preparation, planting and maintenance of new small rubber holdings and for rehabilitating and maintaining existing holdings; builds the capacity of the provincial departments of agriculture to provide effective extension; and selects and trains farmer leaders while carrying out a rubber research program consisting of basic, adaptive, and participatory research, which assesses technical options. Component 2 surveys and maps land in villages and issues land use certificates. Component 3 provides technical support for intensifying crop and livestock production, and strengthens the capacity of extension services; provides a line of credit for sub-loans to help increase farm income from crops and livestock production; pilots fruit tree development, and establishes and monitors nurseries. Component 4 funds training and strengthens the institutional capacities of ethnic minority communities and government departments, and upgrades management skills.
Keywords: Agricultural diversification,Đa dạng hoá nông nghiệp,Agricultural,Nông nghiệp; Production,Sản xuất